Social policy in sub-Saharan African context in search of inclusive development - Adesina, Jimi O (Social policy in a development context, 2007)
This volume reviews Africa's past experiences of social policy, with an eye on the future. Contributions examine a range of social policy issues around healthcare, education, the labour market and social welfare, and highlight conceptual and policy issues for rebuilding Africa.